(untitled) (Bangladesh Journal of Endosurgery, 2014)
Laparoscopic procedure is the gold standard for gallstone diseases. Cholecystoenteric fistula is a rare complication of gallstone diseases and mostly diagnosed during laparoscopic cholecystectomy or open procedure. These conditions can also be treated by laparoscopic method. Out of 4 cases, 2 have been treated by laparoscopic procedure. One is cholecysto-gastric fistula and other is cholecystoduodenal fistula. To close and dissect the tract the authors used suture and plastic clip instead of linear transecting stapler device to cut down cost and minimize the port size without compromising safety. DOI: http://dx.doi.org/10.11593/bje.2013.0103.0018 Bangladesh Journal of Endosurgery Vol.1(3) September 2013: 6-8